A humanidade como pátria - Simões, Francisco; Oliveira, Fabiana Lazzari de; Recio, Liliana Pérez; Borges, Paulo César Balardim (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2025)
Editorial da edição 31